Development of Practical Learning for Virtual Business Simulation Courses in Business Administration Study Program at Medan State Polytechnic - Jumjuma Jumjuma; Agus Mariani Saragih; Nursiah Fitri; Fivi Rahmatus Sofiyah (Budapest International Research and Critics University, 2023)
This study aims to determine the virtual business simulation learning model and then to determine the virtual business simulation learning process design model used by students of the Medan State Polytechnic Business Administration Study Program. Data collection was carried out by making direct observations on Business Administration study programs, especially in classes with the practice of Business Simulation courses. In the second stage, the researcher conducted direct interviews with students, 5th semester Business Administration lecturers who taught the Business Simulation course in accordance with the learning process of the business simulation practice being carried out. Literature study by collecting data and information both from data on the implementation of business simulation courses that have been carried out and those that will be carried out and such as libraries, the internet, literature and previous research related to the problems encountered, researchers observed simulations of business offering practices in class, data analysis was carried out by tabulating data, and processing data by transcribing interview results, coding and interpreting them so that further concluded with a business simulation learning model. The result of the research is the development of virtual business simulation courses by imitating what has been madewww.moonsonsim.com, then carried out in 3 stages, namely: needs analysis, data collection, product design/virtual learning and virtual business simulation learning process design is carried out by: choosing Edmodo which will later be used as a virtual learning tool, preparing photos of learning materials, preparing pointers virtual teaching sentences, setting up virtual teaching creation tools